Therapeutic Interventions in Adult Low-Grade Gliomas - Chammas, Majid (J Clin Neurol, 2019)
Treating adult low-grade gliomas (LGGs) is particularly challenging due to the highly infiltrative nature of this type of brain cancer. Although surgery, radiotherapy, and chemotherapy are the mainstay treatment modalities for LGGs, the optimal combination management plan for a particular patient based on individual symptoms and the risk of treatment-induced toxicity remains unclear. This review highlights the competency and limitations of standard treatment options while providing an essential therapeutic update regarding current clinical trials aimed at implementing targeted therapies with morbidity rates lower than those for current LGG treatments and also augmenting the killing of cancerous cells while maintaining an improved quality of life.